Univerzalnost leptonskega okusa - Plešec, Nikiša (Matrika, 2022)
The Standard Model is a theory, whose predicted interactions between elementary particles match the experimental data very well, however it leaves some phenomena unexplained. New theories that explain deficiencies of the Standard Model are called New Physics. One of the approaches of finding New Physics is through testing the validity of lepton flavour universality, since according to the Standard Model, all leptons participate through weak interaction in the same way, with the same coupling constant GF. Lepton flavour universality is being tested at experiments Belle II and ATLAS, where necessary data is being extracted via reconstruction of an event from the data collected by a detector. New Physics can be found by measuring certain branching fractions, such as R(? /µ), R (D) and R (D*), where a deviation from the Standard Model predictions has already been found. Although current measurements of deviation from the Standard Model predictions are not significant enough to talk about discovering New Physics, there already exist theories that explain it.
Keywords: eksperimentalna fizika; experimental physics; fizika osnovnih delcev; lepton flavour universality; New Physics; Nova fizika; physics of elementary particles; univerzalnost leptonskega okusa